CONTEMPORARY CHALLENGES: LITERATURE, YOUTH, AND TECHNOLOGY - Alves Ramos Nascimento, Joseane (Revista Gênero e Interdisciplinaridade, 2026)
This significant study aimed to understand and reflect on the importance of literature in transforming people, the teaching of literature, and the challenges encountered daily in the classroom. It recognizes that literary reading is important in students’ development and contributes to critical, reflective, and interpretive thinking. However, a resistance is observed among young people who have easy access to technology. In light of this, challenges arise for students seeking knowledge and for teachers who face this reality in the classroom and strive to transform it through meaningful reading strategies.